FEASIBILITY OF MOTORCYCLE LANE APPLICATION IN SUNSET ROAD BALI - - Nicholas; Agah M. Mulyadi (Widyariset, 2012)
Motorcycle population growth more than 12,1% a year in Bali involved in increasing number of motorcycleaccident. To minimized accident rate at road that had high percentage of motorcycle like Sunset Road and 4/2Dtype of geometric a motorcycle lane (MCL) can be applied. Feasibility of MCL Application must fulfil criteriaaccident rate, motorcycle proportion, operational speed, saturation degree (V/C) at peak-hour volume (PHV) andminimum road width. Data of traffic volume and motorcycle speed were collected for 8 hours and analyze withMCL criteria (Idris, 2008) and minimum width road. Sunset Road assumed had motorcycle accident rate 55,6%,motorcycle proportion (pcu) 42% or 500 pcu/hour, operational speed 62 km/hour, V/C= 0,45 and road width 6meters. Compared with the criteria, Sunset Road didn’t fulfilled motorcycle proportion criteria <1.200 pcu/hour,operational speed >44,17 km/hour, V/C <65 and road width <7,5 m, therefore MCL can’t be applied in SunsetRoad.